1971
DOI: 10.1136/jcp.24.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin biosynthesis in the erythrocytes of patients with sideropenic anaemias

Abstract: SYNOPSISThe ability of erythrocytes to synthesize porphyrins from 8-aminolaevulic acid was compared in healthy people, patients with true iron-deficiency anaemia, and anaemic patients with rheumatoid arthritis. Porphyrin synthesis was found to be impaired in true iron deficiency but not in rheumatoid arthritis cases showing a similar degree ofanaemia. The 8-aminolaevulic acid dehydratase activity and the rate of porphobilinogen synthesis did not differ in the three groups studied. The most probable mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1972
1972
1978
1978

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Our results are different from those described by Gutniak, Kopec, and Nieczaj (1971). Their patients with rheumatoid arthritis seem to have a high degree of iron deficiency which is the most reasonable explanation of the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are different from those described by Gutniak, Kopec, and Nieczaj (1971). Their patients with rheumatoid arthritis seem to have a high degree of iron deficiency which is the most reasonable explanation of the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…There is good evidence that in iron deficiency anaemia both globin [21] and haem biosynthesis are disturbed [2,6]. Thus, various authors confirmed that in this condition the free erythrocyte protoporphyrin (EPP) is increased [8,14,16; Lyberatos et cl., unpublished data].…”
mentioning
confidence: 99%
“…(units/ml) (Calissano et al, 1966), mouse liver (Coleman, 1966) and Rhodopseudomonas spheroides (Nandi et al, 1968) has been observed in vitro, it is unlikely to be operative in vivo because of compartmentalization of porphyrin biosynthesis (Sano & Granick, 1961;Sardesai et al, 1965). Reports on 5-aminolaevulinate dehydratase activity in human erythrocytes are opposite and conflicting (Rubino et al, 1960;Lichtman & Feldman, 1963;Battistini et al, 1971;Gutniak et al, 1971;Mazza et al, 1971). In iron-deficient rats the enzyme activity was found to be unaltered when expressed as units/ml of blood, but showed a significant increase when expressed as units/ml of packed erythrocytes.…”
Section: -Aminolaevulinate Excretion Porphobilinogen Excretionmentioning
confidence: 99%